Analisis Kondisi Mental Dan Emosional Remaja Berdasarkan Kuesioner PHQ-9 - Ainil Fitri; Lora Marlita; Andalia Roza; Itto Nesyia Nasution (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2026)
Background: Adolescent mental health represents a critical global public health issue, particularly in light of the increasing incidence of depressive disorders and the heightened risk of suicidal behavior among school-aged youth. The identification of emotional and psychological disturbances at an early stage plays a pivotal role in preventing the progression toward self-harm and suicide. This study aimed to describe the emotional and mental health conditions of adolescents in Pekanbaru City by utilizing the Patient Health Questionnaire-9 (PHQ-9) as a screening instrument. Methods: This research employed a quantitative descriptive approach. Participants were selected through purposive sampling, involving 116 senior high school students. Data collection was conducted using the PHQ-9 questionnaire to determine levels of depressive symptoms and identify potential suicide risk. Results: The results showed that 5% of participants did not exhibit depressive symptoms, while 21% experienced mild depression, 38% moderate depression, 21% moderately severe depression, and 15% severe depression. In addition, 41% of respondents reported experiencing thoughts related to self-harm or suicide. Conclusion: The findings demonstrate that a considerable proportion of adolescents in Pekanbaru City suffer from varying degrees of depression, accompanied by a significant risk of suicidal ideation. This condition underscores the urgent need for increased involvement from educational institutions, healthcare professionals, and families. Efforts to strengthen early screening programs, improve mental health awareness, and expand school-based counseling services are essential to mitigate more severe mental health outcomes in the future.